Shoah in der deutschsprachigen Literatur - Eke, Norbert Otto (Shoah in der deutschsprachigen Literatur)

Furcht und Schrecken im Theater der Erinnerung oder „Man sollte Komödien schreiben / Leben in diesem trüben Menschenbrei“. Heiner Müllers Tragödie - Eke, Norbert Otto (Die deutsche Tragödie. Neue Lektüren einer Gattung im europäischen Kontext)

A combinatorial algorithm for weighted stable sets in bipartite graphs - Faigle, Ulrich; Frahling, Gereon (Discrete Applied Mathematics)
Computing a maximum weighted stable set in a bipartite graph is considered well-solved and usually approached with preflow-push, Ford–Fulkerson or network simplex algorithms. We present a combinatorial algorithm for the problem that is not based on flows. Numerical tests suggest that this algorithm performs quite well in practice and is competitive with flow based algorithms especially in the case of dense graphs.

A fast k-means implementation using coresets - Frahling, Gereon; Sohler, Christian (Proceedings of the twenty-second annual symposium on Computational geometry - SCG '06)
In this paper we develop an efficient implementation for a k-means clustering algorithm. Our algorithm is a variant of KMHybrid [28, 20], i.e. it uses a combination of Lloyd-steps and random swaps, but as a novel feature it uses coresets to speed up the algorithm. A coreset is a small weighted set of points that approximates the original point set with respect to the considered problem. The main strength of the algorithm is that it can quickly determine clusterings of the same point set for many values of k. This is necessary in many applications, since, typically, one does not know a good value for k in advance. Once we have clusterings for many different values of k we can determine a good choice of k using a quality measure of clusterings that is independent of k, for example the average silhouette coefficient. The average silhouette coefficient can be approximated using coresets.To evaluate the performance of our algorithm we compare it with algorithm KMHybrid [28] on typical 3D data sets for an image compression application and on artificially created instances. Our data sets consist of 300,000 to 4.9 million points. We show that our algorithm significantly outperforms KMHybrid on most of these input instances. Additionally, the quality of the solutions computed by our algorithm deviates less than that of KMHybrid.We also computed clusterings and approximate average silhouette coefficient for k=1,…,100 for our input instances and discuss the performance of our algorithm in detail.

Optimal Temporal Partitioning based on Slowdown and Retiming - Plessl, Christian; Platzner, Marco; Thiele, Lothar (Proc. Int. Conf. on Field Programmable Technology (ICFPT))
This paper presents a novel method for optimal temporal partitioning of sequential circuits for time-multiplexed reconfigurable architectures. The method bases on slowdown and retiming and maximizes the circuit's performance during execution while restricting the size of the partitions to respect the resource constraints of the reconfigurable architecture. We provide a mixed integer linear program (MILP) formulation of the problem, which can be solved exactly. In contrast to related work, our approach optimizes performance directly, takes structural modifications of the circuit into account, and is extensible. We present the application of the new method to temporal partitioning for a coarse-grained reconfigurable architecture.
Keywords: temporal partitioning; retiming; ILP

The Effect of Faults on Network Expansion - Bagchi, Amitabha; Bhargava, Ankur; Chaudhary, Amitabh; Eppstein, David; Scheideler, Christian (Theory Comput. Syst.)

Modeling and Investigation of Robot Swarms - Hamann, Heiko

Jean-Monnet Schriftenreihe: Europäisches Wirtschaftsrecht

Geometric spanners with applications in wireless networks - Schindelhauer, Christian; Volbert, Klaus; Ziegler, Martin (Computational Geometry)

Effectively open real functions - Ziegler, Martin (Journal of Complexity)

Uncomputability Below the Real Halting Problem - Meer, Klaus; Ziegler, Martin (Logical Approaches to Computational Barriers)

MedienPädagogik. Zeitschrift für Theorie und Praxis der Medienbildung

d³FACT insight goes parallel - Aggregation of multiple simulations - Dangelmaier, Wilhelm; Huber, Daniel; Laroque, Christoph; Aufenanger, Mark; Fischer, Matthias; Krokowski, Jens; Kortenjan, Michael (Simulation and Visualization 2006 (SimViS))
In this paper the ideas of a new research project are presented. The material flow simu- lator d3FACT insight shall manage multiple parallel and time synchronous simulations to grand the power of real-time visualization in combination with statistical analysis. This research is issued to overcome the conflict of simulation run repetition for a good statistical basis and real-time immersive visualization. A side effect will be the reduc- tion of time needed for simulation experiments. The planned simulation tool has the feature of triggered cloning, i.e., the user can decide during runtime to clone a set of simulations after changing parameters to preserve the original system. The simulations will be aggregated by visualization and statistics. The rendering is planned to overlay several simulations using effects like inking and transparency. Simulation data will be aggregated with statistical functions and diagrams.

Many-body perturbation theory: The GW approximation - Friedrich, Christoph; Schindlmayr, Arno (Computational Condensed Matter Physics)

Time-dependent density-functional theory - Schindlmayr, Arno (Computational Condensed Matter Physics)

Many-body perturbation theory: The GW approximation - Friedrich, Christoph; Schindlmayr, Arno (Computational Nanoscience: Do It Yourself!)
In this lecture we present many-body perturbation theory as a method to determine quasiparticle excitations in solids, especially electronic band structures, accurately from first principles. The main ingredient is the electronic self-energy that, in principle, contains all many-body exchange and correlation effects beyond the Hartree potential. As its exact mathematical expression is unknown, approximations must be used in practical calculations. The approximation is obtained using a systematic algebraic approach on the basis of Green function techniques. It constitutes an expansion of the self-energy up to linear order in the screened Coulomb potential, which describes the interaction between the quasiparticles and includes dynamic screening through the creation of exchange-correlation holes around the bare particles. The implementation of the approximation relies on a perturbative treatment starting from density functional theory. Besides a detailed mathematical discussion we focus on the underlying physical concepts and show some illustrative applications.

Sublinear-time Algorithms - Sohler, Christian; Czumaj, Artur (EATCS Bulletin)

Towards a paradigm for robust distributed algorithms and data structures - Scheideler, Christian (6th International HNI Symposium on New Trends in Parallel and Distributed Computing)

Dynamische Laufzeitprognose bei Extrudergetrieben. Umsetzung ingenieurwissenschaftlichen Wissens in die industrielle Anwendung - Zimmer, Detmar; Bo, Jianquan (Forschungsforum Paderborn - Paderborner Universitätsmagazin)

Methodik zur funktions-, fertigungs- und prüfgerechten Bemaßung und Tolerierung - Denzer, Vera

Steuerreformen und Übergangsprobleme bei Beteiligungsinvestitionen - Sureth-Sloane, Caren

Entwicklung und Inbetriebnahme einer aktiven Federung für ein geländegängiges Nutzfahrzeug - Schäfer, Erika; Jäker, Karl-Peter; Wielenberg, Andreas (3. VDI/VDE-Fachtagung zur Steuerung und Regelung von Fahrzeugen und Motoren)

A Concept for a Platform-Independent Modelling of Mechatronic Systems: Improving the Re-usability of Models in the Mechatronic Design Process - Gambuzza, Alfonso; Koert, Dirk (Postworkshop Proceedings of the 3rd Workshop on Object-oriented Modeling of Embedded Real-Time Systems (OMER3))

Automatische Codegenerierung für verteilte Informationsverarbeitung in mechatronischen Systemen - Gambuzza, Alfonso; Koert, Dirk; Münch, Eckehard; Voecking, Henner (4. Paderborner Workshop Entwurf mechatronischer Systeme)

Reversible Flügelzellenpumpe für aktive Fahrwerkssysteme - Wielenberg, Andreas; Schäfer, Erika (Konstruktion 3/2006)

An EDF-Based, Hard-Real-Time Communication Engine for Distributed Embedded Systems - De Freitas Francisco, Andre L.; Diez, Marcos (IFIP International Conference on Network and Parallel Computing)

RailCab A New Modular Rail System - Rustemeier, Carsten; Nachtigal, Vitalij (4. Internationale wissenschaftliche Konferenz Trans-Mech-Art-Chem)

Self-Coordinating Systems: The Next Challenge in Research on Distributed Systems - Rammig, Franz-Josef; Dangelmaier, Wilhelm; Karl, Holger; Mertsching, Bärbel; Meyer auf der Heide, Friedhelm; Trächtler, Ansgar (New Trends in Parallel & Distributed Computing)

Aktive Fahrwerkssysteme und ihre Vernetzung - Trächtler, Ansgar (12. Esslinger Forum für Kfz-Mechatronik)

Ein integriertes Hardware-in-the-Loop-System zur Funktionsabsicherung von vernetzten Fahrwerksregelsystemen - Nachtigal, Vitalij; Liu-Henke, Xiaobo (3. VDI/VDE-Fachtagung zur Steuerung und Regelung von Fahrzeugen und Motoren)

Iterative Learning and Self-Optimization Techniques for the Innovative RailCab-System - Trächtler, Ansgar; Münch, Eckehard; Voecking, Henner (Proc. 32nd Annual Conference of the IEEE Industrial Electronics Society – IECON)

Observation of Gradients by Means of Algorithmic Differentiation - Münch, Eckehard; Trächtler, Ansgar (Proc. 32nd Annual Conference of the IEEE Industrial Electronics Society – IECON)

Towards Dynamically Reconfigurable Hard-Real-Time Communication for Embedded Mechatronic Systems - De Freitas Francisco, Andre L. (36th Annual IEEE/IFIP International Conference on Dependable System and Networks)

Computer-Aided Education in Mechatronics with a "Window into the Computer" - Toepper, S.; Lückel, Joachim; Trächtler, Ansgar (4 th IFAC-Symposium on Mechatronic Systems)

Modellbasierte Entwicklung vernetzter, mechatronischer Systeme am Beispiel der Konvoifahrt autonom agierender Schienenfahrzeuge - Giese, Holger; Henkler, Stefan; Hirsch, Martin; Tichy, Matthias; Voecking, Henner (4. Paderborner Workshop Entwurf mechatronischer Systeme)

Potential einer Störgrößenaufschaltung bei der Regelung aktiver Fahrwerke am Beispiel eines geländegängigen Nutzfahrzeugs - Schäfer, Erika; Bruns, Torsten; Wielenberg, Andreas (Paderborner Workshop Entwurf Mechatronischer Systeme (EMS))

Model-based Design of an Active Suspension System Equipped with a Reversible Vane Pump - Wielenberg, Andreas; Schäfer, Erika (5th International Fluid Power Conference)

Railcab - mit innovativer Mechatronik zum Schienenverkehrssystem der Zukunft - Trächtler, Ansgar (VDE Kongress)

Modellierung und Optimierung eines Elastomerlagers für ein aktives Federungssystem für PKW - Poddubny, Wladimir (Forschungsbericht, RtM, Universität Paderborn)

Intersection Management as Self-Organisation of Mechatronic Systems - Bruns, Torsten; Münch, Eckehard (6. Internationales Heinz Nixdorf Symposium)

A Breadth-First Approach for Teaching Computer Graphics - Domik, Gitta; Goetz, Frank (EG Education Papers)

Visual Shaditor: A Seamless Way to Compose High-Level Shader Programs - Goetz, Frank; Domik, Gitta (ACM SIGGRAPH 2006 Research Posters)

Design and Construction of a 3D-Scanning-Laservibrometer - Becker, C; Wedman, S; Hemsel, Tobias (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Piezoelectric transducer design via multiobjective optimization - Fu, Bo; Hemsel, Tobias; Wallaschek, Jörg (Ultrasonics)
The design of piezoelectric transducers is usually based on single-objective optimization only. In most practical applications of piezoelectric transducers, however, there exist multiple design objectives that often are contradictory to each other by their very nature. It is impossible to find a solution at which each objective function gets its optimal value simultaneously. Our design approach is to first find a set of Pareto-optimal solutions, which can be considered to be best compromises among multiple design objectives. Among these Pareto-optimal solutions, the designer can then select the one solution which he considers to be the best one. In this paper we investigate the optimal design of a Langevin transducer. The design problem is formulated mathematically as a constrained multiobjective optimization problem. The maximum vibration amplitude and the minimum electrical input power are considered as optimization objectives. Design variables involve continuous variables (dimensions of the transducer) and discrete variables (the number of piezoelectric rings and material types). In order to formulate the optimization problem, the behavior of piezoelectric transducers is modeled using the transfer matrix method based on analytical models. Multiobjective evolutionary algorithms are applied in the optimization process and a set of Pareto-optimal designs is calculated. The optimized results are analyzed and the preferred design is determined.
Keywords: Piezoelectric transducer

Multiobjective optimization of piezoelectric transducers using evolutionary algorithms - Fu, Bo; Hemsel, Tobias; Wallaschek, Jörg (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Dynamic Behaviour of Elastic Bodies Coupled by Extended Friction Contacts - Genzo, Alexander; Sextro, Walter (Proceedings of ISMA - International conference on noise and vibration engineering)
Keywords: Noise; Vibration engineering

Unsteady rolling contact of rubber wheels - Gutzeit, F; Sextro, Walter; Kröger, Matthias (Analysis and Simulation of Contact Problems)
This paper presents a model for unsteady longitudinal slippage of a loaded rubber wheel. The aim of modelling was to calculate the dynamical contact behavior in a numerical efficient way. Further on, simulation results are compared to experimental data.

Powder coating fabrication by ultrasonic standing wave atomizer - Hemsel, Tobias; Henning, C; Kauczor, Christopher; Littmann, Walter (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Control of Bundled Miniature Ultrasonic Linear Motors - Hemsel, Tobias; Mracek, Maik (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Piezoelectric linear motor concepts based on coupling of longitudinal vibrations - Hemsel, Tobias; Mracek, Maik; Twiefel, Jens; Vasiljev, Piotr (Ultrasonics)
Classically, rotary motors with gears and spindle mechanisms are used to achieve translatory motion. In means of miniaturization and weight reduction piezoelectric linear motors are of interest. Several ultrasonic linear motors found in literature base on the use of two different vibration modes. Most often flexural and longitudinal modes are combined to achieve an elliptic micro-motion of surface points. This micro-motion is converted to direct linear (or translatory) motion of a driven slider. To gain high amplitudes of the micro-motion and thus having a powerful motor, the ultrasonic vibrator should be driven near the eigenfrequency of its modes. Additionally, low mechanical and electrical losses lead to increased efficiency and large amplitude magnification in resonance. This demands a geometrical design that fits the eigenfrequencies of the two different modes. A frequency-deviation of only a few percent leads to non-acceptable disturbance of the elliptical motion. Thus, the mechanical design of the vibrators has to be done very carefully. Within this contribution we discuss different motor designs based on the coupling of two the same longitudinal vibrations within one structure to generate an elliptic motion of surface points. Different concepts based on piezoelectric plates and Langevin transducers are compared. Benefits and drawbacks against the combination of longitudinal and bending modes will be discussed. Numerical results of the stator vibration as well as motor characteristics are validated by measurements on different prototypes.
Keywords: Piezoelectric linear motor

Model Based Analysis of Piezoelectric Transformers - Hemsel, Tobias; Priya, S (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Model based analysis of piezoelectric transformers - Hemsel, Tobias; Priya, S (Ultrasonics)
Piezoelectric transformers are increasingly getting popular in the electrical devices owing to several advantages such as small size, high efficiency, no electromagnetic noise and non-flammable. In addition to the conventional applications such as ballast for back light inverter in notebook computers, camera flash, and fuel ignition several new applications have emerged such as AC/DC converter, battery charger and automobile lighting. These new applications demand high power density and wide range of voltage gain. Currently, the transformer power density is limited to $40 W/cm{^3}$ obtained at low voltage gain. The purpose of this study was to investigate a transformer design that has the potential of providing higher power density and wider range of voltage gain. The new transformer design utilizes radial mode both at the input and output port and has the unidirectional polarization in the ceramics. This design was found to provide 30 W power with an efficiency of 98% and 30 $\,^{°}$C temperature rise from the room temperature. An electro-mechanical equivalent circuit model was developed to describe the characteristics of the piezoelectric transformer. The model was found to successfully predict the characteristics of the transformer. Excellent matching was found between the computed and experimental results. The results of this study will allow to deterministically design unipoled piezoelectric transformers with specified performance. It is expected that in near future the unipoled transformer will gain significant importance in various electrical components.
Keywords: Piezoelectric transformers

Error-Workspace Analysis of Plane Mechanisms - Hofmeisterro, Adolf; Sextro, Walter; Röschel, Otto (Proceedings of EUCOMES, the first European Conference on Mechanism Science)

Focusing cross-fire applicator for ultrasonic hyperthermia of tumors - Lierke, E.G.; Hemsel, Tobias (Ultrasonics)
An improved concept for ultrasonic hyperthermia of tumors is presented. This concept is based on past experience of a German government supported project [1], which ended in 1984. It offers a low cost alternative to common RF- and microwave methods for hyperthermia of tumors with volumes between 1 and 40 ml at treatment times between 30 and 60 min. Our new version of the system considerably improves the temperature suppression in the healthy tissue around the target area and enables the adjustment of the beam width to the actual tumor size and the field geometry to the depth and shape of the tumor. The applicator can be used for moderate hyperthermia with tissue overheating up to 10 K or for ablation therapy with short high temperature pulses. Its central area is free for the integration of a commercial ultrasonic diagnostic sector scanner or a Doppler flow sensor in order to support the adjustment of the transducer and to monitor the whole area during the therapy.
Keywords: Moderate hyperthermia

Focussing Cross-Fire Applicator for Ultrasonic Hyperthermia of Tumors - Lierke, Ernst-Günter; Hemsel, Tobias (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Powder Transport by Ultrasonic Waves - Mracek, B; Hemsel, Tobias; Mracek, Maik (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Synergetic driving concepts for bundled miniature ultrasonic linear motors - Mracek, Maik; Hemsel, Tobias (Ultrasonics)
Rotary ultrasonic motors have found broad industrial application in camera lens drives and other systems. Linear ultrasonic motors in contrast have only found limited applications. The main reason for the limited range of application of these very attractive devices seems to be their small force and power range. Attempts to build linear ultrasonic motors for high forces and high power applications have not been truly successful yet. To achieve larger force and higher power, multiple miniaturized motors can be combined. This approach, however, is not as simple as it appears at first glance. The electromechanical behaviour of the individual motors differs slightly due to manufacturing and assembly tolerances. The individual motor characteristics are strongly dependent on the driving parameters (frequency, voltage, temperature, pre-stress, etc.) and the driven load and the collective behaviour of the swarm of motors is not just the linear superposition of the individual drive's forces. Thus, the bundle of motors has to be synchronized and controlled appropriately in order to obtain an optimized drive that is not oversized and costly. We have investigated driving and control strategies of a set of linear ultrasonic motors. Our contribution will be divided into three main parts. In part I ultrasonic linear motors will be introduced. In part II driving strategies for a single motor as well as for a bundle of motors will be presented. These concepts will be verified by simulation results and experimental data. In part III a simplified model for the motor's electromechanical behaviour will be given.
Keywords: Ultrasonic linear motor

Self configuration of a novel miniature ultrasonic linear motor - Mracek, Maik; Vasiljev, Piotr; Hemsel, Tobias; Wallaschek, Jörg (Solid State Phenomena)

Model based design of piezoelectric generators utilizing geometrical and material properties - Richter, Björn; Twiefel, Jens; Hemsel, Tobias; Wallaschek, Jörg (ASME 2006 International Mechanical Engineering Congress and Exposition)
This paper presents a general model based on the electromechanical circuit theory. The model is set up as a mechanical equivalent model for base excited systems and describes the behaviour of a piezoelectric element around one resonance frequency which is sufficient for most practical applications. The model is extended to obtain the influence of geometrical and material properties. The derivated properties are used to describe the parameters of the general model which is easy to handle. Using this model either the calculation of the output power on a specific electric load or the determination of the design of the used piezoelectric element for a needed electric output power is possible. The paper focuses on the design of the ratio of length and width of a piezoelectric bimorph. The validity of the model is shown by the comparison of computed and experimental results.
Keywords: Materials properties; Design; Generators

Comparison of Piezoelectric and Shape Memory Alloy Based Actuators - Schiedeck, Florian; Hemsel, Tobias (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

The use of shape memory alloy wires in actuators - Schiedeck, Florian; Hemsel, Tobias; Wallaschek, Jörg (Solid State Phenomena)

Contact behaviour of a sliding rubber element - Sextro, Walter; Moldenhauer, Patrick; Wangenheim, M; Lindner, Markus; Kröger, Matthias (Analysis and Simulation of Contact Problems)
Friction occurs in the contact between tyre and road. The friction of rubber material on dry surfaces is dominated by hysteresis and adhesion effects. Hysterisis friction is characterised by the energy dissipation within the visco-elastic material, which is caused by its deformation while passing the surface roughness. Hysteresis effects are modelled by an extended linear visco-elastic material with several Maxwell elements. The development of a model in the time domain allows to consider nonlinear effects. Additionally temperature effects are taken into account based on the WLF-transformation. Adhesion forces originate from molecular bindings between the contact partners. This effect is simulated by applying a modified model of Achenbach on real surfaces. The temperature distribution within the friction contact region is investigated experimentally as well. Furthermore global stick-slip vibrations of a rubber block element are investigated using a global contact model. Numerical results are compared with experiments performed on a tribometer test rig.

Energy harvesting with piezoelectric Elements - Twiefel, Jens; Hemsel, Tobias; Kauczor, Christopher (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Model-based design of piezoelectric energy harvesting systems
In the design process of energy harvesting systems based on piezoelectric elements, achievable energy output is the most interesting factor. To estimate this amount a priori manufacturing of prototypes a mathematical model is very helpful. Within this contribution we will introduce a model based on electro-mechanical circuit theory. Its parameters are identified by measurements and the model is validated by comparison to experimental results. The model is designed to support the development-engineer in the dimensioning of energy harvesting units to specific application demands. Two main challenges in device design are investigated with the mathematical model: influence of the ambient excitation frequency, and influence of the load impedance. Typically, the equivalent model approach delivers models for piezoelectric elements that are driven in resonance by electrical excitation. In the case of energy harvesting the piezoelectric elements are excited mechanically and most often non-resonant. Thus, we first set up a mechanical equivalent model for base excited systems. In first approximation it represents an energy harvesting unit around one resonance frequency. The model is expandable for a wider frequency range using the superpositioning of multiple circuits. From the viewpoint of optimum energy transformation between mechanical and electrical energy it is favorable to drive piezoelectric elements at resonance or anti-resonance. Thus, an energy harvesting system should be tuned to the excitation frequency.

Non-resonant piezoelectric motors driven in audible frequency range - Wilmanns, S; Nakamura, K; Mracek, Maik; Hemsel, Tobias (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Piezoelectrics in dental tools - Zhou, W; Fu, Bo; Hemsel, Tobias; Wallaschek, Jörg (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Proceedings of the Workshop on Model Driven Development of Advanced User Interfaces, satellite of the MoDELS 2006 conference

Fairness Considerations in Replication and Placement Strategies for large Documents in heterogeneous Content Delivery Networks - Loeser, Christoph; Schomaker, Gunnar; Schubert, Matthias; Schattkowsky, Tim (Proceedings of the 5th International Conference on Networking (ICN 2006), Morne (Mauritius))

Secure Storage for Physically Exposed Web- and Application Servers - Schattkowsky, Tim; Förster, Alexander; Loeser, Christoph (Proceedings of the 5th International Conference on Networking (ICN 2006), Morne (Mauritius))

Using UML Activities for System-on-Chip Design and Synthesis - Schattkowsky, Tim; Hendrik Hausmann, Jan; Engels, Gregor (Proceedings of the International Conference on Model Driven Engineering Languages and Systems (MoDELS 2006), Genova (Italy))

Workshop Report: Model Driven Development of Advanced User Interfaces (MDDAUI) - Pleuß, Andreas; Van den Bergh, Jan; Sauer, Stefan; Hußmann, Heinrich (Satellite Events at the MoDELS 2005 Conference, MoDELS 2005 International Workshops, Doctoral Symposium, Educators Symposium, Revised Selected Papers, Montego Bay (Jamaica))

Generating Instance Models from Meta Models - Ehrig, Karsten; Taentzer, Gabriele; Küster, Jochen; Winkelmann, Jessica (Proceedings of the conference on Formal Methods for Open Object-Based Distributed Systems (FMOODS 2006), Bologna (Italy))

Combining Analysis of Unstructured Workflows with Transformation to Structured Workflows - Hauser, Rainer; Friess, Michael; Küster, Jochen; Vanhatalo, Jussi (Proceedings of the 10th IEEE International Enterprise Distributed Object Computing Conference (EDOC 2006))

Teaching UML Is Teaching Software Engineering Is Teaching Abstraction - Engels, Gregor; Hendrik Hausmann, Jan; Lohmann, Marc; Sauer, Stefan (Proceedings of the Satellite Events at the MoDELS 2005 Conference, Montego Bay (Jamaica))
As the Unified Modeling Language (UML) has by now seen widespread and successful use in the software industry and academia alike, it has also found its way into many computer science curricula. An outstanding advantage of teaching UML is that it enables an illustration of many crucial concepts of software engineering, far beyond its concrete notation. Most important among these concepts is that of abstraction. We present a course design which demonstrates the use of UML as a vehicle for teaching such core concepts of software engineering. Multimedia elements and tools help to efficiently convey the courses message to the students.

Model-Driven Monitoring: An Application of Graph Transformation for Design by Contract - Engels, Gregor; Lohmann, Marc; Sauer, Stefan; Heckel, Reiko (Proceedings of the 3rd International Conference on Graph Transformation (ICGT 2006), Natal (Brazil))
The model-driven development (MDD) approach for constructing software systems advocates a stepwise refinement and transformation process starting from high-level models to concrete program code. In contrast to numerous research efforts that try to generate executable function code from models, we propose a novel approach termed model-driven monitoring. Here, models are used to specify minimal requirements and are transformed into assertions on the code level for monitoring hand-coded programs during execution. We show how well-understood results from the graph transformation community can be deployed to support this model-driven monitoring approach. In particular, models in the form of visual contracts are defined by graph transitions with loose semantics, while the automatic transformation from models to JML assertions on the code level is defined by strict graph transformation rules. Both aspects are supported and realized by a dedicated Eclipse plug-in.

A Pattern-driven Development Process for Quality Standard-conforming Business Process Models - Förster, Alexander; Schattkowsky, Tim; Engels, Gregor; Van Der Straeten, Ragnhild (IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC 2006), Brighton (UK))

Model-driven Monitoring: Generating Assertions from Visual Contracts - Lohmann, Marc; Engels, Gregor; Sauer, Stefan (Proceedings of the 21st IEEE International Conference on Automated Software Engineering (ASE 06), Tokyo (Japan))
The Visual Contract Workbench is a tool that supports model-driven development of software systems by lifting the Design by Contract idea, which is usually used at the code level, to the model level. It uses visual contracts for graphically specifying the pre- and post-conditions of an operation. Java classes with JML (Java Modeling Language) assertions are generated from visual contracts to facilitate automatic monitoring of the correctness of the programmer's implementation.

Industrielle Fallstudie: Einsatz visueller Kontrakte in serviceorientierten Architekturen - Engels, Gregor; Güldali, Baris; Juwig, Oliver; Lohmann, Marc; Richter, Jan-Peter (Proceedings of the conference on Software Enginneering, Fachtagung des GI Fachbereichs Softwaretechnik (SE 2006), Leipzig (Germany))
Serviceorientierte Architekturen (SOA) erlauben eine schnelle und kosteneffiziente Bereitstellung unterschiedlicher Funktionalitäten zur Unterstützung der Geschäftsprozesse eines Unternehmens. Dazu werden fachliche Funktionalitäten in Form von Enterprise Services zur Verfügung gestellt. Die hohe Zahl von Enterprise Services erfordert eine geeignete semantische Beschreibung zu deren effizienten Verwaltung. Zur semantischen Beschreibung von Enterprise Services sowie zur Formulierung von Suchanfragen ist an der Universität Paderborn die Methode der visuellen Kontrakte entwickelt worden. Das Papier stellt die Ergebnisse der ersten Phase einer umfangreichen industriellen Fallstudie zur Evaluation der praktischen Anwendbarkeit visueller Kontrakte im Kontext einer SOA vor.

Semantische Beschreibung von Enterprise Services – Eine industrielle Fallstudie - Lohmann, Marc; Richter, Jan-Peter; Engels, Gregor; Güldali, Baris; Juwig, Oliver; Sauer, Stefan

Adaptations of Renewable Energy Policies to unstable macroeconomic situations – Case study: Wind power in Brazil - Kissel, J.; Krauter, Stefan (Energy Policy)

Optical modelling and simulation of PV module encapsulation to improve structure and material properties for maximum energy yield - Krauter, Stefan; Grunow, Paul (Proceedings of the 4th World Conference on Photovoltaic Energy Conversion (Joint congress of IEEE/PVSEC/EUPVC), Waikoloa, Hawaii (USA), 8.–12. Mai 2006, S. 2133–2137)

Modelling the encapsulation factors for photovoltaic modules - Grunow, Paul; Krauter, Stefan (Proceedings of the 4th World Conference on Photovoltaic Energy Conversion (Joint congress of IEEE/PVSEC/EUPVC), Waikoloa, Hawaii (USA), 8.–12. Mai 2006, S. 2152–2155. Best Poster Award by IEEE.)

Solar Electric Power Generation - Krauter, Stefan

Optical simulation to enhance PV module encapsulation - Krauter, Stefan; Grunow, Paul (Proceedings of the 21st European Photovoltaic Solar Energy Conference and Exhibition, Dresden, 4.–8. September 2006, S. 2065–2068)

Book of Proceedings of RIO 6 – World Climate & Energy Event

Transaktionshäufigkeit als Indikator für die Angebotsgestaltung bei deutschen Online-Brokern. 45 (1), 20-38. - Kundisch, Dennis; Krammer, A. (Der Markt - Zeitschrift für Absatzwirtschaft und Marketing)

Deutsche Personalchefs erobern zunehmend die Geschäftsleitung - Brewster, C; Kabst, Rüdiger

HR Outsourcing: Ein trojanisches Pferd für die Personalfunktion - Kabst, Rüdiger

HR의 목표는 비용절감이 아니라 서비스의 질을 높이는 것입니다 (Das Ziel von HR-Outsourcing ist nicht nur Kosten zu reduzieren, sondern die Qualität der Dienstleistung zu erhöhen) - Kabst, Rüdiger

Internationales Personalmanagement im deutschen Mittelstand - Kabst, Rüdiger; Maiazza, K m

Internationalisierung mittelständischer Unternehmen: Fünf Thesen zum Auslandsmarkterfolg - Kabst, Rüdiger

Personalarbeit im Vergleich - Brewster, C; Kabst, Rüdiger

Status und Professionalisierung des deutschen Personalmanagements: Ist Besserung in Sicht? - Kabst, Rüdiger; Giardini, A

Einführung in die Betriebswirtschaftslehre - Weber, W; Kabst, Rüdiger

Downsizing: Theoretische Zugänge und empirische Evidenz - Weller, I; Kabst, Rüdiger (Beschäftigungspolitk von Unternehmen: Theoretische Erklärungsansätze und empirische Befunde)

Vertrauen, Opportunismus, Kontrolle: Eine empirische Analyse von Joint Venture Beziehungen vor dem Hintergrund der Transaktionskostentheorie. - Eberl, P; Kabst, R (Management von Netzwerkorganisationen)

Virtualization of HRM: Human resources in network and loosely structured organizations - Kabst, Rüdiger; Strohmeier, S (European Human Resource Management)

Virtualization: Boundaryless organizations and electronic human resource management - Kabst, Rüdiger; Strohmeier, S (Managing Human Resources in Europe)

Early versus Late Internationalizers: Meta-Analytic Results of the Determinants of Internationalization - Schwens, C; Kabst, Rüdiger

How Early Internationalizers Learn: Experience from Others and Paradigms of Interpretation - Schwens, C; Kabst, Rüdiger